Plasmodium falciparum Infection Status among Children with Schistosoma in Sub-Saharan Africa: A Systematic Review and Meta-analysis. - Abraham Degarege; Dawit Degarege; Emir Veledar; Berhanu Erko; Mathieu Nacher; Consuelo M Beck-Sague; Purnima Madhivanan (PLoS Neglected Tropical Diseases)
Background It has been suggested that Schistosoma infection may be associated with Plasmodium falciparum infection or related reduction in haemoglobin level, but the nature of this interaction remains unclear. This systematic review synthesized evidence on the relationship of S. haematobium or S. mansoni infection with the occurrence of P. falciparum malaria, Plasmodium density and related reduction in haemoglobin level among children in sub-Saharan Africa (SSA). Methodology/principal findings A systematic review in according with PRISMA guidelines was conducted. All published articles available in PubMed, Embase, Cochrane library and CINAHL databases before May 20, 2015 were searched without any limits. Two reviewers independently screened, reviewed and assessed all the studies. Cochrane Q and Moran's I2 were used to assess heterogeneity and the Egger test was used to examine publication bias. The summary odds ratio (OR), summary regression co-efficient (β) and 95% confidence intervals (CI) were estimated using a random-effects model. Out of 2,920 citations screened, 12 articles (five cross-sectional, seven prospective cohort) were eligible to be included in the systematic review and 11 in the meta-analysis. The 12 studies involved 9,337 children in eight SSA countries. Eight studies compared the odds of asymptomatic/uncomplicated P. falciparum infection, two studies compared the incidence of uncomplicated P. falciparum infection, six studies compared P. falciparum density and four studies compared mean haemoglobin level between children infected and uninfected with S. haematobium or S. mansoni. Summary estimates of the eight studies based on 6,018 children showed a higher odds of asymptomatic/uncomplicated P. falciparum infection in children infected with S. mansoni or S. haematobium compared to those uninfected with Schistosoma (summary OR: 1.82; 95%CI: 1.41, 2.35; I2: 52.3%). The increase in odds of asymptomatic/uncomplicated P. falciparum infection among children infected with Schistosoma remained significant when subgroup analysis was conducted for S. haematobium (summary OR: 1.68; 95%CI: 1.18, 2.41; I2: 53.2%) and S. mansoni (summary OR: 2.15; 95%CI: 1.89, 2.46: I2: 0.0%) infection. However, the density of P. falciparum infection was lower in children co-infected with S. haematobium compared to those uninfected with Schistosoma (summary-β: -0.14; 95% CI: -0.24, -0.01; I2: 39.7%). The mean haemoglobin level was higher among children co-infected with S. haematobium and P. falciparum than those infected with only P. falciparum (summary-mean haemoglobin difference: 0.49; 95% CI: 0.04, 0.95; I2: 66.4%). Conclusions/significance The current review suggests S. mansoni or S. haematobium co-infection may be associated with increased prevalence of asymptomatic/uncomplicated P. falciparum infection in children, but may protect against high density P. falciparum infection and related reduction in haemoglobin level.